Dinamika Peran Nahdlatul Ulama Dalam Pengembangan Pendidikan Islam Tradisional Dan Modern Di Indonesia - Nurasisah; Selvi Nur Aninsi; Idrus L (Tamilis Synex: Multidimensional Collaboration, 2026)
This study examines the dynamics of Nahdlatul Ulama's (NU) role in the development of traditional and modern education in Indonesia. As the world's largest Islamic organization, NU maintains an extensive educational network encompassing thousands of pesantren, madrasahs, and formal institutions ranging from primary to higher education levels. Employing a qualitative approach through literature review and historical-comparative analysis, this research investigates the transformation of NU's educational role from its founding in 1926 to the contemporary era. The findings reveal that NU has successfully preserved traditional pesantren-based educational values (tafaqquh fiddin) while integrating a modern curriculum attuned to contemporary needs. Through its educational arm, Ma'arif NU, the organization has fostered an integrative educational model that harmoniously combines religious and general sciences. These dynamics are inextricably linked to challenges posed by modernization, globalization, and evolving national education policies. In conclusion, NU emerges as a strategic agent of educational transformation, effectively bridging tradition and modernity within the Indonesian context.